Adaptation of the south-west wing of Collegium Chemicum of Adam Mickiewicz University in Poznań for storage facilities = Adaptacja południowo-zachodniego skrzydła budynku Collegium Chemicum UAM w Poznaniu na cele magazynowe - Ścigałło, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article refers to the problems of adaptation of Collegium Chemicum facilities belonging to Adam Mickiewicz Uniwersity in Poznań to its storage needs. The subject building is situated in Grunwaldzka Street in Poznań. In the introduction part, the building and its structural solutions are described. The results of the materials research and the measurements of the used reinforcement have been presented.
Keywords: konstrukcje żelbetowe; adaptacja; analiza diagnostyczna; wzmacnianie; reinforced concrete structures; construction analysis; adaptation; strengthened